Production of Alginate Oligosaccharides (AOSs) Using Enhanced Physicochemical Properties of Immobilized Alginate Lyase for Industrial Application - Simranjeet Kaur; Reinu E. Abraham; Christopher M. M. Franco; Munish Puri (Marine Drugs, 2024)
Alginate lyase (AL) is a polysaccharide-degrading enzyme that can degrade alginate by hydrolyzing glycosidic bonds and produces unsaturated alginate oligosaccharides (AOSs). These AOSs have wide therapeutic and nutraceutical applications. However, to produce alginate oligosaccharides in a cost-effective manner is challenging due to the low availability and high cost of this degrading enzyme. Immobilization of the enzyme facilitates industrial applications owing to its stability, reusability, and cost-effectiveness. This study was focused on the enhancement of the properties of alginate lyase and improvement of the production of AOS. Alginate lyase was immobilized on magnetic nanoparticles (NPs) using glutaraldehyde as the crosslinker. The study showed that the maximum binding achieved between NPs and protein in the enzyme was 71% at a ratio of 1:150 NP:protein. As a result of immobilization, the optimum activity of free enzyme which was obtained at 37 °C and pH 7.4 changed to 45 °C and pH 9. Furthermore, the enzyme was thermostable at 45 °C for 3 h with up to 50% reusability for six consecutive cycles. Storage stability after 15 days showed ~67% relative hydrolysis of alginate. The free alginate lyase (25 IU) showed 76% raw biomass (seaweed) hydrolysis which is higher compared to 63% provided by the immobilized enzyme. As a result of efficient hydrolysis, AOSs with molecular weight profile of 370–1040 kDa were produced and detected using HPLC.